The correlation between interleukin-1β levels and aggressive periodontitis: A scoping review - Agus Susanto; Yanti Rusyanti; Nu'ty Hasya Chinta Andari Effendi (Wolters Kluwer Medknow Publications, 2023)
Aggressive periodontitis is a multifactorial disease; the body's immune response is one of the factors that contributed to the disease development. One of the responses is in the form of the secretion of cytokines-that is, interleukin-1β (IL-1β). The secretion of the said cytokine influences the development of periodontitis, particularly the occurrence of rapid bone loss. This study aimed to confirm whether there is a correlation between the levels of IL-1β and the severity of aggressive periodontitis from collected sources. The research performed is a type of literature review that employs the scoping review method to map the results of the analysis from among the topics discussed. Article searches were performed on four databases-PubMed, Cochrane Library, Google Scholar, and Science Direct-using keywords with the Boolean Operators method. In addition, a manual search was also performed. The articles were selected with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Review (PRISMA-ScR) flow in accordance with the predetermined inclusion and exclusion criteria. This led to the collection of 10 relevant articles, which were reviewed by reviewing the levels of IL-1β in an individual with aggressive periodontitis. In addition, how much bone damage occurs is seen through the depth of the pocket. Eight of ten articles showed a correlation between levels of IL-1β and bone loss in aggressive periodontitis. Elevated IL-1β levels in patients with aggressive periodontitis reveal a correlation with the severity of the disease that is bone loss.